2020
DOI: 10.1177/1056787920963650
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Systems Thinking in Schools: Mental Models of School Management Teams

Abstract: Systems thinking (ST) is a holistic leadership approach that puts the study of wholes before that of parts. It focuses attention on how organization members act together in networks of interactions. This is done by researching organization members’ mental models, which are deeply ingrained assumptions, generalizations, or even mental pictures or images that influence how one understands the world and thus takes action in order to achieve desired results. The purpose of this study was to explore the ST of schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
5
0
1
Order By: Relevance
“…The relationships between TMX and LMX The current study focuses on the quality of the exchange relationships among the SMT members and their relationships with their principal at the team-level. SMTs in schools are workgroups consisting of senior personnel, such as deputy principals, grade-level and disciplinary coordinators and the school principal who typically serves as the team leader (Chen-Levi et al, 2021). The SMT members interact to shape their schools' objectives and policies as well as being responsible for achieving school goals (Arar and Nasra, 2020).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…The relationships between TMX and LMX The current study focuses on the quality of the exchange relationships among the SMT members and their relationships with their principal at the team-level. SMTs in schools are workgroups consisting of senior personnel, such as deputy principals, grade-level and disciplinary coordinators and the school principal who typically serves as the team leader (Chen-Levi et al, 2021). The SMT members interact to shape their schools' objectives and policies as well as being responsible for achieving school goals (Arar and Nasra, 2020).…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…Principals have increasingly come to rely on the functioning of school management teams (SMT) for achieving school outcomes (Benoliel and Somech, 2016). SMTs are organized in interdisciplinary teams to which managerial duties are delegated, and are responsible for the day-to-day running of the school as well as shaping school policies (Chen-Levi et al, 2021). Under these conditions, scholars suggest a viewpoint that is focused on the role of quality of team exchange relationships at work in coping adaptively with the challenges and bringing about desired work outcomes (Chen et al, 2023;Seers et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies indicate that PST creates a positive work environment in the school that facilitates positive team attitudes and behaviors such as teachers' job satisfaction, organizational commitment and empowering professional learning communities (McGurk and Pearson, 2018; Vidal, 2023). It was also found that PST promotes a common positive sense of shared work and responsibility within the SMT (Chen-Levi et al ., 2021). Recent research suggests that PST may influence the SMT as a whole and have an impact on teamwork processes and outcomes (McCaughan and Palmer, 2018).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Lebih jauh lagi bahwa untuk mencapai predikat sekolah efektif maka memerlukan implementasi dari learning organization di sekolah. Implementasi learning organization terdiri dari beberapa komponen di antaranya system thinking, personal mastery, mental models, shared vision, dan team learning (Senge, 1994;Chen-Levi, Schechter and Buskila, 2021). Kelima komponen tersebut sangat penting sebagai dasar dari organisasi belajar (Senge, 1990) Pemimpin merupakan seseorang yang memiliki kekuasaan untuk mengatur organisasi yang dipimpinnya, kemampuan untuk memengaruhi, dan menentukan tujuan organisasi (Musgar, 2019;Starlinsky, Belawati and Rosita, 2022).…”
Section: Pendahuluanunclassified